2010
DOI: 10.4269/ajtmh.2010.10-0339
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the pfmdr1 Gene and In Vitro Artemether and Lumefantrine Sensitivity in Thai Isolates of Plasmodium falciparum

Abstract: We evaluated the influence of pfmdr1 mutations and copy number on in vitro artemether and lumefantrine sensitivity in 101 laboratory and adapted Thai isolates of Plasmodium falciparum. Approximately one-fourth of these isolates exhibited reduced lumefantrine susceptibility. We found that both mutations and amplification of the pfmdr1 gene influenced in vitro artemether and lumefantrine sensitivity. Using multivariate analysis, 184F or 1042N alleles and a copy number of ≥ 4 were identified as the independent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
44
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 31 publications
7
44
1
Order By: Relevance
“…Given the widespread nature of samples with K13-propeller mutations and slow clearance following artesunate treatment [5], there is concern that artesunate–mefloquine efficacy will be compromised across a wider area of Thailand in the near future. These data match previously published data from a distinct area of the Thailand–Cambodia border [39, 46]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Given the widespread nature of samples with K13-propeller mutations and slow clearance following artesunate treatment [5], there is concern that artesunate–mefloquine efficacy will be compromised across a wider area of Thailand in the near future. These data match previously published data from a distinct area of the Thailand–Cambodia border [39, 46]. …”
Section: Discussionsupporting
confidence: 91%
“…Isolates with amplified pfmdr1 were also seen in Ranong (southern Thailand–Myanmar border), consistent with previous data [3941]. Analysis of genome-wide genetic similarity shows that parasites from the Thailand–Myanmar border and central Myanmar (Shwe Kyin) are related; it is worth noting that most patients enrolled in Mae Sot travelled from Myanmar, with the catchment area extending as far as 40 km inside the border [7].…”
Section: Discussionsupporting
confidence: 86%
“…Studies in South East Asia have shown that the amplification of mdr1 gene is associated with mefloquine [16] and possibly lumefantrine resistance [28]. Our findings support the suggestion that mdr1 amplification is rare in Africa [23].…”
Section: Discussionsupporting
confidence: 88%
“…An investigation of laboratory and adapted Thai isolates identified pfmdr1 184F or 1042N alleles and a copy number of ‡4 to be associated with decreased sensitivity to lumefantrine in vitro [158]. A study in Ghana looked at pfmdr1 copy number over time and, although amplification was observed, this was not associated with any reports of resistance [115].…”
Section: Lumefantrine Resistancementioning
confidence: 99%